Помпова інсулінотерапія у дітей із цукровим діабетом 1-го типу: клінічні спостереження - Глоба, Є. В.; Зелінська, Н. Б.; Погадаєва, Н. Л. (Clinical Endocrinology and Endocrine Surgery, 2011)
In the article the clinical cases of positive clinical experience in patients with diabetes mellitus type 1 are given. Continuous subcutaneous insulin infusion was prescribed in connection with glycemic control with high risk, often acute and heavy chronic complications in children with multiple daily insulin injections.